Evaluation of Cements Curing Modes Regarding Microleakage During Cementation of E-max Laminate Veneers - Alqahtani, Waleed; Galal, Rami Mohammed; Hamza, Ghada (Open Access Macedonian Journal of Medical Sciences, 2021)
Purpose: The aim of this study is to investigate the effect of the curing modes of two adhesive resin cements (Light cure mode of the Variolink Veneer, the self-cure mode and dual cure mode of the Multilink Automix) on the marginal leakage of lithium disilicate ceramic laminate veneers. Methods: A total number of forty eight extracted natural central incisors were prepared to receive ceramic laminate veneers, constructed using E-max ceramic divided into three groups cemented using three curing modes of two adhesive resin cements {light-cure mode of Variolink Veneer, self-cure mode of Multilink Automix and dual-cure mode of Multilink Automix adhesive resin cements} . Die penetration test was done using the methylene blue stain {qualitative assessment} for testing the die penetration along the tooth/ceramic interface. Results: Descriptive statistical analysis revealed that the self-curing mode recorded the significantly least degree of leakage compared to the light and dual cure modes. The self-cure mode recorded (0.1±0.3) which was significantly lower than light cure (1.2 ±0.9) and dual cure mode (1.2 ±0.4), there was no statistical significant difference between the later two curing modes. The self-cure mode of the resin cement is considered a more effective method for having the least marginal leakage at the tooth/ceramic interface. There was no difference between the light cure mode and the dual cure mode.